Deliberate choices or strong motives: Exploring the mechanisms underlying the bias of organic claims on leniency judgments. (1st August 2016) - Prada, Marília; Rodrigues, David; Garrido, Margarida V.
Abstract: Organic claims can influence how a product is perceived in dimensions that are unrelated with the food production method (e.g., organic food is perceived as more healthful and less caloric than conventional food). Such claims can also bias how the consumers of organic food are perceived and how other people judge their behavior. Schuldt and Schwarz (2010) have shown that individuals evaluating a target with a weight-loss goal are more lenient in judging the target forgoing exercise when the target had an organic (vs. conventional) dessert. This impact of organic claims on leniency judgments has been interpreted either as a halo or a licensing effect. In the current research we aim to replicate and extend Schuldt and Schwarz's (2010) results by examining the mechanisms that are more likely to explain the observed leniency judgments. In Experiment 1, we observed that leniency towards a target that has consumed an organic meal is only observed when the target intentionally chooses such organic meal (vs. choice determined by the situation). These findings suggest that the impact of organic claims on leniency judgments is not merely based on a halo effect. Instead, a licensing account emerges as the most probable mechanism. In Experiment 2, we further found that stronger (vs. weaker) motives for forgoing exercise influenced leniency judgments to the same extent as having had an organic meal. Understanding the mechanisms that shape consumers' decisions may have important implications to prevent bias in their judgments about food and exercise. Highlights: Organic claims bias judgments in dimensions unrelated to food production method. Organic claims promote higher leniency towards forgoing exercising. Eating organic only promotes leniency if the target intentionally choses the meal (vs. choice determined by the situation). Perceivers are sensitive to situational constraints: high leniency when the target has stronger (vs. weaker) motives. Overall results suggest a licensing account as the mechanism responsible for the organic claims bias on leniency judgments.